Animals in the Romanesque sculpture of Norman cathedrals - Pilgrim, Esther (2018)
This dissertation takes four of the great Norman churches and studies the Romanesque animal sculptures in and on them in order to come to conclusions about why certain animals may have been represented in different places. An overview of humoral theory, medieval bestiaries, and the relations between humans and animals in the medieval period in chapters two and three helps to gain an appreciation of how animals were viewed and their associations at the time. Chapters 5-8 then give a brief description of each church and present the Romanesque animal sculptures found during surveys and desktop research. This information is then used to map out the animal sculptures onto church plans in order to find patterns in their distribution. The following chapters then use the information from bestiaries, humoral theory, and the Bible in order to show that there are patterns in where the animal sculptures appear around the churches, through mapping, and come to conclusions as to why these patterns may have been created.